2003
DOI: 10.1080/00207450390161903
|View full text |Cite
|
Sign up to set email alerts
|

Aromas of Rosemary and Lavender Essential Oils Differentially Affect Cognition and Mood in Healthy Adults

Abstract: This study was designed to assess the olfactory impact of the essential oils of lavender (Lavandula angustifolia) and rosemary (Rosmarlnus officinalis) on cognitive performance and mood in healthy volunteers. One hundred and forty-four participants were randomly assigned to one of three independent groups, and subsequently performed the Cognitive Drug Research (CDR) computerized cognitive assessment battery in a cubicle containing either one of the two odors or no odor (control). Visual analogue mood questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
285
3
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(314 citation statements)
references
References 29 publications
17
285
3
9
Order By: Relevance
“…An interesting comparison can be made to the results of the current study to those reported by Moss et al, (2003) regarding the effects of rosemary and lavender aromas on the same cognitive and mood assessments. Lavender aroma was found to produce decrements in performance on secondary memory, speed of memory and speed of attention compared to controls.…”
Section: Contentednessmentioning
confidence: 68%
See 1 more Smart Citation
“…An interesting comparison can be made to the results of the current study to those reported by Moss et al, (2003) regarding the effects of rosemary and lavender aromas on the same cognitive and mood assessments. Lavender aroma was found to produce decrements in performance on secondary memory, speed of memory and speed of attention compared to controls.…”
Section: Contentednessmentioning
confidence: 68%
“…In a previous investigation, Moss et al (2003) compared cognitive performance across lavender, rosemary or control conditions using a computerised assessment battery.…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary aroma has a similar action (Moss and Cook 2003 35. Eight hours of sleep may also double the probability of acquiring insights into the solutions of problems (Wagner et al 2004).…”
Section: Chaptermentioning
confidence: 88%
“…The disinfectant and medicinal properties of lavender can be used in different market sectors, such as the cosmetics and industrial fragrance industries, among others (Al-Amier et al, 1999;Shellie et al, 2002;Moss et al, 2003;Beus, 2006;Chemat et al, 2006;Dob et al, 2006;Singh et al, 1997).…”
Section: Introductionmentioning
confidence: 99%